Evaluasi kesesuaian penyimpanan obat di gudang farmasi puskesmas Ngesrep berdasarkan standar kefarmasian dan Syariat Islam - Rini , Tri Diana Puspita; Rochajati , Siti; Najmi , Tusti Naida Pavita (Journal of Pharmaceutical and Sciences, 2025)
Pharmaceutical services are direct services and communication to patients related to pharmaceutical preparations to achieve definite results and improve patients' quality of life. Drug storage is the activity of storing and maintaining by placing received drugs in a place that is considered safe from theft and physical disturbances that can damage the quality of the drug. If there is an error in storing the drug, it will decrease the drug content and result in losses to the Health Center. This study was conducted to distribute the storage of pharmaceutical preparations in the Ngesrep Health Center pharmacy installation warehouse. This study is a type of non-experimental research, namely descriptive research conducted through observation and interviews related to storing pharmaceutical preparations through evaluation based on Permenkes Number 74 of 2016 and the Directorate General of Pharmacy and Medical Devices and analysis of drug storage indicators. Based on the results of the study, it was obtained that the suitability of the spatial storage requirements at the Ngesrep Health Center in 2024 was 90.74%, with excellent information.